The Welfare State Scattergram - Askola, Joni; Davison, Benjamin (Politologija, 2023)
Welfare states have traditionally been studied through quantitative tools such as indices and qualitative ones such as typologies. However, there seems to be a lack of analytical tools that simultaneously show welfare state outcomes and development potential. In this paper, we developed the Welfare State Scattergram. This result of two indices gives the welfare state’s outcomes and fiscal capacity, the latter serving as a proxy for improvement potential. The indicator used for the X-axis is a modified debt-sustainability formula to indicate fiscal capacity and, thus, the development potential of the welfare state. The indicator used for the Y-axis gives the welfare state outcomes and consists of a weighted welfare state outcomes indicator.
Keywords: Welfare State; Welfare State Outcomes; Fiscal Capacity; Scattergram; Index Creation